ANALISIS PENGARUH CAPITAL ADEQUACY RATIO (CAR), OPERATIONAL EFFICIENCY (BOPO), DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP RETURN ON ASSET (ROA), (STUDI KASUS PADA BPR DI KOTA JAYAPURA) - Ahadi Rerung (ark:/00000/jeb.v13i2, 2022)
This research is a case study on BPR in Jayapura to analyze the effect of CAR, BOPO, LDR on ROA. This study aims to determine whether there is an effect of CAR, BOPO, LDR on ROA at BPR in Jayapura. The population used in this study is the financial statements of BPR Banks in the city of Jayapura, namely 3 banks, namely BPR Irian Sentosa, BPR Papua Mandiri Makmur, BPR Phidectama, the period 2017 to 2020. This study uses data collection techniques through library techniques. The analytical method used is multiple linear regression using SPSS version 20.00 for Windows. Based on the results of the study, it shows that CAR has a significant effect on ROA with a t-count value of 2.123 > t-table value of 1.680. While BOPO and LDR have no significant effect on ROA. It can be seen from the t-count value of BOPO of -1.749 < t-table value of 1.680 and the t-value of LDR of 0.764 <t-table value of 1.680. But CAR, BOPO, and LDR together (simultaneously) affect the ROA of BPR Banks for the 2017-2020 period.